COVID-19 crisis interlinkage with past pandemics and their effects on food security - Hynek Roubík; Michal Lošťák; Chama Theodore Ketuama; Jana Soukupová; Petr Procházka; Adam Hruška; Josef Hakl; Lukáš Pacek; Petr Karlík; Lucie Kocmánková Menšíková; Vladimíra Jurasová; Charles Amarachi Ogbu; et al. (BMC, 2023)
Abstract Background Pandemics as health and humanitarian crises have exerted traceable impacts on food security. Almost all past and current pandemics have created a food crisis that affects a share of the global population and threaten global food security. With the more frequent outbreaks of emerging and re-emerging diseases or pandemics, this paper looks at the various types of impacts from the current coronavirus crisis and past pandemics to identify their major impact on food security. Scope To this effect, key strategies that could be put in place to ensure the efficient resilience of food systems before, during, and after the pandemics to mitigate the negative impact of the pandemics on global food security are recommended. The most recent effects of the current coronavirus crisis have been disruptions in the flow of farm labourers and inefficient farm operations leading to postharvest food losses. Key findings and conclusions Modification of diets between social groups has also been observed. Future response orientations to prevent and mitigate the effects of pandemics on food security will consider pro-active and adapted policy, program, and institutional actions towards the systemic development of global food systems as an interconnected network.